Information disorder and organic food purchasing behavior: A moderated mediation model - Zheng, Yan; Cao, Dayu (Frontiers in Nutrition, 2022)
On the one hand, fast social media and internet evolution has brought opportunities to the development of the organic food industry. On the other hand, the excessive utilization of social media and internet has also exerted some negative effects on consumers in terms of information disorder and hindered the industrial progression of organic foods. This study aimed to probe into the associations among organic food information uncertainty, information search anxiety, information overload and purchase behaviour, which were mediated by attitude and moderated by involvement. Under this issue, the information disorder concept was proposed. The data (cross-sectional) of 620 organic food consumers in Jiangxi Province, China were subjected to SEM (structural equation modelling). The results showed that organic food information uncertainty and information search anxiety significantly affected attitude, and attitude had a positive impact on purchase behaviour. In addition, attitude significantly mediated the effects of organic food information uncertainty and information search anxiety on purchase behaviour. Moreover, the indirect relationship between organic food information uncertainty and purchase behaviour was moderated by involvement.